2020
DOI: 10.1039/c9ew01124b
|View full text |Cite
|
Sign up to set email alerts
|

Graphene stimulates the nucleation and growth rate of NaCl crystals from hypersaline solution via membrane crystallization

Abstract: Advanced graphene engineered membranes designed for sustainable crystallization of high-quality crystals from hypersaline water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 75 publications
3
15
0
Order By: Relevance
“…This behaviour is in agreement with what recently observed for GPNs (UW) 35 and suggested there was no inertia of graphene towards water vapour but rather a supporting action in the diffusion process. This experimental evidence is unquestionably corroborated by the literature, which refers to a certain aptitude of graphene to interact with water molecules [42][43][44][45]72 with indications from the adsorption of water vapour on exfoliated GPNs of up to 249 cm 3 g À1 at 20 C, 42 the adsorption of water on the edge of graphene through the dissociation of H 2 O to an H atom and OH group, 71 the increased work adhesion between water and the membrane surface modied with GPNs. 45 Herein, Raman spectroscopy gave an indication of the presence of defects due to the edges of the WJM akes (Fig.…”
Section: Membrane Distillation Testssupporting
confidence: 70%
See 2 more Smart Citations
“…This behaviour is in agreement with what recently observed for GPNs (UW) 35 and suggested there was no inertia of graphene towards water vapour but rather a supporting action in the diffusion process. This experimental evidence is unquestionably corroborated by the literature, which refers to a certain aptitude of graphene to interact with water molecules [42][43][44][45]72 with indications from the adsorption of water vapour on exfoliated GPNs of up to 249 cm 3 g À1 at 20 C, 42 the adsorption of water on the edge of graphene through the dissociation of H 2 O to an H atom and OH group, 71 the increased work adhesion between water and the membrane surface modied with GPNs. 45 Herein, Raman spectroscopy gave an indication of the presence of defects due to the edges of the WJM akes (Fig.…”
Section: Membrane Distillation Testssupporting
confidence: 70%
“…Considering that the membranes exhibited a more or less comparable porosity and thickness but a smaller mean pore size for the FLG-WJM(0.65) membrane, it is reasonable to suppose an involvement of the nanoller in the mass transfer through the membranes. 35,45,71 Table 2 shows the MD transport coefficients (B) calculated for the two FLG-WJM membranes. In both cases, the trend uctuated independently of the difference in the partial pressure applied across the membranes.…”
Section: Membrane Distillation Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the presence of fillers in PVDF-based membranes reduced the time for detection of the first clearly visible crystals in comparison with PVDF-pristine membrane, from 285 min to 140 min in the case of PVDF/BT (0.5%) (Figure 6). The obtained experimental results agree with the findings of Perrotta et al [7,17], where it was suggested that well-established interactions at the graphene-solution interface stimulate water sequestration from ion-water clusters and promote ion-ion aggregation. As a consequence, reduced nucleation time and increased growth rate of the crystals can be detected in the PVDF/G (0.5%) with respect to the pristine PVDF membrane (sample 1, Table 3).…”
Section: Membrane Crystallization Testssupporting
confidence: 91%
“…In the 2010s, a new method called membrane-assisted crystallization was proposed for simultaneous water production using membrane technology and recovery of dissolved compounds in the solid form by its crystallization from saturated solutions [ 32 ]. This approach is compelling because of its compactness, lesser metal consumption, and greater flexibility in the process operation, and it was already utilized for crystallization of inorganic salts [ 33 , 34 ] and organic compounds [ 35 ] using pressure-driven processes of solution concentration (reverse osmosis, nanofiltration) as well as evaporation processes (pervaporation, membrane distillation). The membrane distillation (MD) can be considered one of the effective approaches for the concentration of different kinds of brines with moderate or high salinity [ 36 ].…”
Section: Introductionmentioning
confidence: 99%